2006
DOI: 10.2319/11405-398
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance of Erbium-doped Yttrium Aluminum Garnet Laser–Treated and Phosphoric Acid–Etched Enamels

Abstract: Objective:To compare the effects of erbium-doped yttrium aluminum garnet (Er:YAG) laser ablation and of phosphoric acid etching on the in vitro acid resistance of bovine enamel. Materials and Methods: Teeth were polished to make the surface flat. The polished enamel was either etched with 37% phosphoric acid for 30 seconds or ablated with a single 33 J/cm 2 pulse from an Er:YAG laser. The control specimens were free from acid etching and laser ablation. Changes in crystal structure, dissolved mineral (calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
2
44
2
Order By: Relevance
“…This result is similar in part to those of Cardoso and others, 33 who reported no change in microshear bond strength for the ''all-in-one'' adhesive used in their study but in part contrasts with reported significant lowering of bond strength of the two-step adhesive to enamel following Er,Cr:YSGG laser ablation compared with diamond bur-cut enamel. Kim and others 28 reported increased resistance to acid etching of Er:YAGirradiated enamel. Hossain and others 29 reported a significant increase in calcium and phosphate concentrations in irradiated dentin at the cavity floor following Er,Cr:YSSG irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is similar in part to those of Cardoso and others, 33 who reported no change in microshear bond strength for the ''all-in-one'' adhesive used in their study but in part contrasts with reported significant lowering of bond strength of the two-step adhesive to enamel following Er,Cr:YSGG laser ablation compared with diamond bur-cut enamel. Kim and others 28 reported increased resistance to acid etching of Er:YAGirradiated enamel. Hossain and others 29 reported a significant increase in calcium and phosphate concentrations in irradiated dentin at the cavity floor following Er,Cr:YSSG irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…11,[22][23][24][25][26][27] Increased resistance to acid etching of Er:YAG-irradiated enamel has been reported. 28 Other authors have reported a significant increase in calcium and phosphate concentrations in irradiated dentin at the cavity floor following erbium, chromium:yttrium, scandium, gallium, garnet (Er,Cr:YSSG) irradiation. 29 Another study reported a significant increase in quantities of calcium in Er,Cr:YSSG-irradiated canine mandibular bone, although the calcium:phosphate ratio was not significantly affected.…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 However, its use could be justified by the fact that several studies 11,14,15 reported that enamel Er:YAG laser results in a suitable micro retentive pattern for adhesion and can increase enamel acid resistance, 9,15-17 contrary to acid etching which demineralizes enamel surface leading to caries. 15,18 Additionally, it is also thought to have an antibacterial effect by entrapping free ions 12,18,19 and forming remineralization microspaces. 12,19 Nevertheless, laser treatment requires specific considerations as the use of correct tip, 8,15,20 adequate energy, otherwise could result in sub or over ablative energy, causing either flacking 8,18,21,22 or vitrification.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Additionally, it is also thought to have an antibacterial effect by entrapping free ions 12,18,19 and forming remineralization microspaces. 12,19 Nevertheless, laser treatment requires specific considerations as the use of correct tip, 8,15,20 adequate energy, otherwise could result in sub or over ablative energy, causing either flacking 8,18,21,22 or vitrification. 8,20 Furthermore, dental tissues response depends on several conditions such as focal distance, irriga- tion, among others; 15,23 in addition, ablation process could lead to produce a microretentive surface on enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the surface roughness alone may not be a contributing factor, and the quality of the enamel left behind may also play a major factor for bonding of restoration to enamel. 36,37 • During cavity preparation, laser works by causing microexplosions in enamel surface, leading to formation of microcracks. However, these crack propagations are not uniform and their depth is variable.…”
Section: Discussionmentioning
confidence: 99%